Protective and Detrimental Role of Heme Oxygenase-1 - Sorrenti, Valeria (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The book "Protective and Detrimental Role of Heme Oxygenase-1", includes a selection of original research papers and reviews aimed at understanding the dual role (protective and detrimental) of HO-1 and the involved signaling pathways. Original research papers and reviews aimed at the identification of natural molecules or new synthetic compounds able to modulate HO-1 activity/expression help make HO-1 a potential therapeutic target for the amelioration of various diseases.